Preparation method of probe card substrate
By using spinel and calcium titanate composite materials to prepare probe card substrates, the problems of high dielectric loss and insufficient anti-electromagnetic interference capability in the prior art are solved, and low dielectric loss and excellent anti-electromagnetic interference performance are achieved to meet the high-performance testing needs.
Patent Information
- Application Number
- CN202411570372.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-25
AI Technical Summary
The existing probe card substrate has high dielectric loss in high-frequency signal transmission, which is difficult to meet the needs of high-performance testing. At the same time, the anti-electromagnetic interference capability is insufficient, which affects the stability and reliability of the test.
A composite material of spinel and calcium titanate is used to ball mill and press into composite raw ceramic sheets through a high-energy ball mill, followed by drilling and photoresist coating to form a probe card substrate.
It reduces dielectric loss, improves anti-electromagnetic interference capability, enhances the low dielectric loss and anti-electromagnetic interference performance of the probe card substrate, and meets the needs of high-performance integrated circuit testing.
Smart Images

Figure CN119504250A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wafer testing, and in particular to a method for preparing a probe card substrate. Background Art
[0002] In the field of modern integrated circuit testing and packaging, probe cards are widely used as a key testing tool in the electrical performance testing of semiconductor chips. The main function of the probe card is to contact the test points on the chip to be tested through the tiny probes on it to achieve signal transmission and testing. The probe card has a probe card substrate and one or more needles. The needle is contacted to the pad of the component connected to the semiconductor chip, so that the semiconductor component detection equipment sends and receives electrical signals to the pad of the component through the needle of the probe card connected to the probe card substrate, thereby judging whether the component is defective or not.
[0003] The performance of the probe card directly affects the accuracy, speed and stability of the test. The probe card substrate, as the support and signal transmission basis of the probe card, plays a vital role in the comprehensive performance of the probe card through its material properties, manufacturing process and structural design. Among them, the substrate not only carries the probe array, but also is responsible for the transmission and distribution of signals. Common substrate materials include ceramics, polymers, composite materials, etc. Each material has its own unique advantages and disadvantages. For example, ceramic substrates are widely used due to their good thermal stability and mechanical strength.
[0004] During high-frequency signal transmission, the dielectric loss of the substrate material will directly affect the integrity and transmission efficiency of the signal. High dielectric loss will lead to increased signal attenuation, increase test errors, and affect the accuracy of test results. Although the dielectric constant of traditional ceramic substrates is low, the dielectric loss is still high at high frequencies, which makes it difficult to meet the needs of high-performance testing. At the same time, with the continuous improvement of the integration of integrated circuits, the electromagnetic environment faced during the test process is becoming increasingly complex. As a medium for signal transmission, the anti-electromagnetic interference ability of the probe card substrate directly affects the stability and reliability of the test. Some existing substrate materials perform poorly in terms of anti-electromagnetic interference and are easily interfered by external electromagnetic signals, resulting in distorted test results or test failures.
[0005] Therefore, it is necessary to improve the deficiencies in the prior art to solve the above problems. Summary of the invention
[0006] The present invention aims at the deficiencies of the existing probe card substrate in terms of dielectric loss and anti-electromagnetic interference, and provides a method for preparing a probe card substrate.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a probe card substrate, comprising the following steps:
[0008] S1. Place spinel powder and calcium titanate powder of a certain mass ratio in a high-energy ball mill, add a certain amount of polyvinyl alcohol for ball milling, and dry to obtain a mixed powder;
[0009] S2, pressing the mixed powder into a green body of a desired shape under a certain pressure, and sintering the green body to form a composite green ceramic sheet;
[0010] S3, grinding and polishing the surface of the composite green porcelain sheet, and drilling;
[0011] S4, placing the punched composite green ceramic sheet in a spin coater, coating it evenly with photoresist, baking it, exposing it with ultraviolet light of a certain wavelength, developing it, and cleaning it to obtain a probe card substrate.
[0012] In a preferred embodiment of the present invention, in step S1, the mass ratio of the spinel powder to the calcium titanate powder is 1:1-3; the particle size of the spinel powder is 30-100 μm, and the tap density is 3-5 g / cm 3 The particle size of the calcium titanate powder is 1 to 3 μm, and the tap density is 3 to 6 g / cm 3 .
[0013] In a preferred embodiment of the present invention, in step S1, the content of polyvinyl alcohol is 3-10wt%; the ball milling time is 2-4h; the drying temperature is 50-60°C and the drying time is 1-2h.
[0014] In a preferred embodiment of the present invention, in the step S2, the pressure is 70-80 MPa; the green body is disc-shaped, with a diameter of 30-50 mm and a thickness of 5-6 mm.
[0015] In a preferred embodiment of the present invention, in the step S2, the sintering temperature is 1300-1480° C., and the sintering time is 2-5 hours.
[0016] In a preferred embodiment of the present invention, in step S3, the punching is specifically to form circular holes penetrating the surface of the composite green ceramic sheet by laser punching, and the diameter of the circular holes is 30-120 μm.
[0017] In a preferred embodiment of the present invention, in the step S4, the photoresist is one of i-line photoresist and KrF photoresist, and the coating thickness is 0.5-5 μm.
[0018] In a preferred embodiment of the present invention, in the step S4, the temperature of the heat drying is 80-120° C. and the time is 1-2 min.
[0019] In a preferred embodiment of the present invention, in step S4, the wavelength of the ultraviolet light is one of 248 nm and 365 nm, and the energy of the exposure is 200 to 3500 mJ / cm 2 .
[0020] In a preferred embodiment of the present invention, in the step S4, the development uses a tetramethylammonium hydroxide developer, the development temperature is 15 to 25° C., and the development time is 10 to 50 seconds.
[0021] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0022] (1) The present invention provides a method for preparing a probe card substrate. By using a composite of spinel and calcium titanate, both of which are ionic crystals, and spinel is an equiaxed crystal system with similar symmetry, the atoms and ions at the interface can easily obtain the lowest energy stable arrangement, so that they form a tight bond, reduce the interface energy, help reduce defects and gaps at the interface, and improve the stability of the composite interface. The ordered and stable structure can reduce the scattering and collision of electrons during transmission, maintain the stability of the dielectric constant, and reduce dielectric loss. At the same time, the characteristics of the molecular structure and spatial arrangement of spinel and calcium titanate make them highly resistant to interference from electromagnetic waves, so that the prepared probe card substrate has excellent low dielectric loss and anti-electromagnetic interference capabilities.
[0023] (2) In the present invention, the appropriate mass ratio of spinel to calcium titanate avoids the effect of low or high calcium titanate content, which causes the inability to form a stable composite structure with spinel and the synergistic effect, so that it can form a stable composite structure and a tight particle arrangement to obtain the best dielectric properties and anti-electromagnetic interference performance.
[0024] (3) In the present invention, a probe card substrate with low dielectric loss and excellent anti-electromagnetic interference capability is prepared, which effectively avoids the signal integrity and transmission efficiency affected by dielectric loss, and the test stability and reliability affected by electromagnetic interference, thereby meeting the needs of high-performance integrated circuit testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 The present invention is a flow chart of a method for preparing a probe card substrate according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0029] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained through the preparation methods of existing technologies.
[0030] like Figure 1 As shown, a method for preparing a probe card substrate comprises the following steps:
[0031] S1. Place spinel powder and calcium titanate powder of a certain mass ratio in a high-energy ball mill, add a certain amount of polyvinyl alcohol for ball milling, and dry to obtain a mixed powder;
[0032] S2, pressing the mixed powder into a green body of a desired shape under a certain pressure, and sintering the green body to form a composite green ceramic sheet;
[0033] S3, grinding and polishing the surface of the composite green porcelain sheet, and drilling;
[0034] S4, placing the punched composite green ceramic sheet in a spin coater, coating it evenly with photoresist, baking it, exposing it with ultraviolet light of a certain wavelength, developing it, and cleaning it to obtain a probe card substrate.
[0035] In some specific embodiments, in step S1, the mass ratio of spinel powder to calcium titanate powder is 1:1-3; the particle size of the spinel powder is 30-100 μm, and the tap density is 3-5 g / cm 3 ; The particle size of calcium titanate powder is 1-3 μm, and the tap density is 3-6 g / cm 3 .
[0036] In some specific embodiments, in step S1, the content of polyvinyl alcohol is 3-10 wt %; the ball milling time is 2-4 h; the drying temperature is 50-60° C., and the drying time is 1-2 h.
[0037] In some specific embodiments, in step S2, the pressure is 70-80 MPa; the green body is disc-shaped with a diameter of 30-50 mm and a thickness of 5-6 mm.
[0038] In some specific embodiments, in step S2, the sintering temperature is 1300-1480° C., and the sintering time is 2-5 hours.
[0039] In some specific implementation schemes, in step S3, the punching is specifically to form circular holes penetrating the surface of the composite green ceramic sheet by laser punching, and the diameter of the circular holes is 30-120 μm.
[0040] In some specific embodiments, in step S4, the photoresist is one of i-line photoresist and KrF photoresist, and the coating thickness is 0.5-5 μm.
[0041] In some specific embodiments, in step S4, the temperature of the heat drying is 80-120° C., and the time is 1-2 min.
[0042] In some specific embodiments, in step S4, the wavelength of the ultraviolet light is one of 248 nm or 365 nm, and the exposure energy is 200-350 mJ / cm 2 .
[0043] In some specific embodiments, in step S4, tetramethylammonium hydroxide developer is used for development, the development temperature is 15 to 25° C., and the development time is 10 to 50 s.
[0044] The following is a detailed description of the overall implementation of the present invention in conjunction with specific examples.
[0045] Example 1
[0046] A method for preparing a probe card substrate comprises the following steps:
[0047] S1. Place spinel powder and calcium titanate powder in a mass ratio of 1:2 in a high-energy ball mill, add 8 wt% polyvinyl alcohol, ball mill for 3 h, and dry at 60° C. for 1 h to obtain a mixed powder;
[0048] S2, pressing the mixed powder into a disc-shaped green body with a diameter of 50 mm and a thickness of 6 mm under a pressure of 75 MPa, and sintering the green body at a temperature of 1450° C. for 4 hours to form a composite green ceramic sheet;
[0049] S3, grinding and polishing the surface of the composite green porcelain sheet, and using laser drilling to form a circular hole with a pore size of 50 μm and penetrating the surface of the composite green porcelain sheet;
[0050] S4, place the punched composite green ceramic sheet in a spin coater, evenly coat it with a negative KrF photoresist with a thickness of 2 μm, heat bake it at 100°C for 1 min, use a mask to partially shield the photoresist, control the exposure line, use deep ultraviolet light with a wavelength of 248 nm and a power of 300 mJ / cm 2 The photoresist was exposed to light with energy of , and a tetramethylammonium hydroxide developer was used at a temperature of 20° C. for 20 seconds to remove the unexposed photoresist, and the photoresist was cleaned to obtain a probe card substrate.
[0051] The particle size of the spinel powder is 50 μm and the tap density is 3.58 g / cm 3 ; The particle size of calcium titanate powder is 2.5μm and the tap density is 4.1g / cm 3 .
[0052] Example 2
[0053] This embodiment is basically the same as Embodiment 1, except that: Step S1 is as follows: placing spinel powder and calcium titanate powder in a mass ratio of 1:1 in a high-energy ball mill, adding 8 wt% polyvinyl alcohol, ball milling for 3 h, and drying at 60°C for 1 h to obtain a mixed powder.
[0054] Example 3
[0055] This embodiment is basically the same as Embodiment 1, except that: Step S1 is as follows: placing spinel powder and calcium titanate powder in a mass ratio of 1:1.5 in a high-energy ball mill, adding 8 wt% polyvinyl alcohol, ball milling for 3 h, and drying at 60°C for 1 h to obtain a mixed powder.
[0056] Example 4
[0057] This embodiment is basically the same as Embodiment 1, except that: Step S1 is as follows: placing spinel powder and calcium titanate powder in a mass ratio of 1:2.5 in a high-energy ball mill, adding 8 wt% polyvinyl alcohol, ball milling for 3 h, and drying at 60°C for 1 h to obtain a mixed powder.
[0058] Example 5
[0059] This embodiment is basically the same as Embodiment 1, except that: Step S1 is as follows: placing spinel powder and calcium titanate powder in a mass ratio of 1:3 in a high-energy ball mill, adding 8 wt% polyvinyl alcohol, ball milling for 3 h, and drying at 60°C for 1 h to obtain a mixed powder.
[0060] Comparative Example 1
[0061] This comparative example is basically the same as Example 1, except that: Step S1 is: placing spinel powder and calcium titanate powder in a mass ratio of 2:1 in a high-energy ball mill, adding 8wt% polyvinyl alcohol, ball milling for 3h, and drying at 60°C for 1h to obtain a mixed powder.
[0062] Comparative Example 2
[0063] This comparative example is basically the same as Example 1, except that: Step S1 is: placing spinel powder and calcium titanate powder in a mass ratio of 1:4 in a high-energy ball mill, adding 8wt% polyvinyl alcohol, ball milling for 3h, and drying at 60°C for 1h to obtain a mixed powder.
[0064] Performance testing: The probe card substrates obtained in the above-mentioned Examples 1-6 and Comparative Examples 1-2 were subjected to performance tests of dielectric loss and anti-electromagnetic interference performance in turn.
[0065] Dielectric loss test: refer to T / CSTM 00910-2022 "Dielectric constant and dielectric loss tangent test method of high-frequency dielectric substrate - stripline test method".
[0066] Anti-electromagnetic interference test: Use network analyzer to test the highest electromagnetic shielding effectiveness value in the X-band.
[0067] The dielectric loss and anti-electromagnetic interference performance test results of the probe card substrates of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1.
[0068] Table 1:
[0069]
[0070]
[0071] As shown in Table 1, through the performance tests of Examples 1-5, it can be learned that by adopting the composite of spinel and calcium titanate, both of which are ionic crystals, and spinel is an equiaxed crystal system with similar symmetry, the atoms and ions at the interface can easily obtain the lowest energy stable arrangement, so that they form a tight bond, reduce the interface energy, help reduce defects and voids at the interface, and improve the stability of the composite interface. The ordered and stable structure can reduce the scattering and collision of electrons during transmission, maintain the stability of the dielectric constant, and reduce dielectric loss. At the same time, the characteristics of the molecular structure and spatial arrangement of spinel and calcium titanate make them have strong resistance to interference from electromagnetic waves, so that the prepared probe card substrate has excellent low dielectric loss and anti-electromagnetic interference capabilities.
[0072] By comparing Example 1 with Comparative Examples 1 and 2, it can be learned that when the content of calcium titanate is low, it is unable to effectively form a stable composite structure with spinel and is unable to fully fill the voids, resulting in loose connections between particles. The voids and defects will become obstacles to charge transfer, resulting in uneven charge distribution, increased dielectric loss, and reduced anti-electromagnetic interference performance. When the content of calcium titanate is high, it is easy to occupy too much space and interfere with the normal arrangement of spinel particles, weakening the interaction between spinel particles, thereby reducing the overall performance of the probe card substrate. Therefore, a suitable mass ratio of spinel and calcium titanate is selected so that it can form a stable composite structure and tight particle arrangement to obtain the best dielectric properties and anti-electromagnetic interference performance.
[0073] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0074] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a probe card substrate, characterized in that: The following steps are involved: S1. Place spinel powder and calcium titanate powder of a certain mass ratio in a high-energy ball mill, add a certain amount of polyvinyl alcohol for ball milling, and dry to obtain a mixed powder; S2, pressing the mixed powder into a green body of a desired shape under a certain pressure, and sintering the green body to form a composite green ceramic sheet; S3, grinding and polishing the surface of the composite green porcelain sheet, and drilling; S4, placing the punched composite green ceramic sheet in a spin coater, coating it evenly with photoresist, baking it, exposing it with ultraviolet light of a certain wavelength, developing it, and cleaning it to obtain a probe card substrate.
2. The method for preparing a probe card substrate according to claim 1, characterized in that: In step S1, the mass ratio of the spinel powder to the calcium titanate powder is 1:1-3; the particle size of the spinel powder is 30-100 μm, and the tap density is 3-5 g / cm 3 The calcium titanate powder has a particle size of 1 to 3 μm and a tap density of 3 to 6 g / cm 3 .
3. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S1, the content of the polyvinyl alcohol is 3-10 wt %; the ball milling time is 2-4 h; the drying temperature is 50-60° C., and the drying time is 1-2 h.
4. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S2, the pressure is 70-80 MPa; the green body is disc-shaped, with a diameter of 30-50 mm and a thickness of 5-6 mm.
5. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S2, the sintering temperature is 1300-1480° C. and the sintering time is 2-5 hours.
6. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S3, the punching is specifically to form circular holes penetrating the surface of the composite green ceramic sheet by laser punching, and the diameter of the circular holes is 30-120 μm.
7. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S4, the photoresist is one of i-line photoresist and KrF photoresist, and the coating thickness is 0.5-5 μm.
8. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S4, the temperature of the heat drying is 80-120° C. and the time is 1-2 minutes.
9. The method for preparing a probe card substrate according to claim 1, characterized in that: In step S4, the wavelength of the ultraviolet light is 248 nm or 365 nm, and the exposure energy is 200 to 3500 mJ / cm 2 .
10. The method for preparing a probe card substrate according to claim 1, characterized in that: In the step S4, the development uses a tetramethylammonium hydroxide developer, the development temperature is 15 to 25° C., and the development time is 10 to 50 seconds.